A Complete Design And Development Of A Miniature Battery-Less Power Management Unit For Powering Biomedical Implant - Wong, Yan Chiew; Yap, Jim Hui (Taylor’s University, 2021)
With the emerging of micro and nanotechnology in energy harvesting system, small size, self-powered, fully integrated on-chip battery-less power management system is preferable. However, a miniature power management system with an ultra-low input voltage as well as low kick- start voltage is the challenging task in the research. For this reason, a single inductor based dynamic closed loop battery-less power management systemis proposed by using only 30 mV or 1 °C from the thermoelectric generator to boost up to a minimum of 1.2V. Different topology of miniature boost converters in terms of input voltage, start-up voltage and form factor were reviewed. The focus highlighted on different configurations of CMOS switch inductor boost converter used within energy harvesting circuitry. The design has been developed in 130 nm Silterra CMOS process technology and only occupies an area of 1.00593